2018
DOI: 10.7189/jogh.08.010406
|View full text |Cite
|
Sign up to set email alerts
|

Carrying water may be a major contributor to disability from musculoskeletal disorders in low income countries: a cross-sectional survey in South Africa, Ghana and Vietnam

Abstract: BackgroundThe Sustainable Development Goals include commitments to end poverty, and promote education for all, gender equality, the availability of water and decent work for all. An important constraint is the fact that each day, many millions of women and children, and much less frequently men, carry their household’s water home from off-plot sources. The burden of fetching water exacerbates gender inequality by keeping women out of education and paid employment. Despite speculation about the potential health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
92
1
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(108 citation statements)
references
References 43 publications
7
92
1
1
Order By: Relevance
“…In much of the world, women are the primary household water managers (Cole & Ferguson, ; Sultana & Loftus, ), just as they are often the primary preparers of food (Wutich & Brewis, ). A recent meta‐analysis of 42 studies found that there is moderate quantitative evidence and strong qualitative evidence to demonstrate that carrying water heightens fatigue and other physical ailments (Geere et al, ; Geere, Cortobius, Geere, Hammer, & Hunter, ). Many households that access off‐plot water require women and girls to negotiate water source access, walk to public sources, transfer water into containers, and carry it to their homes for use and storage.…”
Section: How Might Household Water Insecurity Exacerbate Food Insecurmentioning
confidence: 99%
“…In much of the world, women are the primary household water managers (Cole & Ferguson, ; Sultana & Loftus, ), just as they are often the primary preparers of food (Wutich & Brewis, ). A recent meta‐analysis of 42 studies found that there is moderate quantitative evidence and strong qualitative evidence to demonstrate that carrying water heightens fatigue and other physical ailments (Geere et al, ; Geere, Cortobius, Geere, Hammer, & Hunter, ). Many households that access off‐plot water require women and girls to negotiate water source access, walk to public sources, transfer water into containers, and carry it to their homes for use and storage.…”
Section: How Might Household Water Insecurity Exacerbate Food Insecurmentioning
confidence: 99%
“…Ingestion of contaminated water produces a range of viral (eg, hepatitis A), bacterial (eg, cholera), and protozoal (eg, amoebiasis) diseases; 2.4 million deaths annually are believed to be preventable with improved water provision, sanitation, and hygiene (Bartram & Cairncross, ). The act of carrying water can result in pain and disability related to excess loads, falls, assaults, and other traumas (Geere et al, ; Sorensen, Morssink, & Campos, ). Water insecurity also has indirect effects on growth and development.…”
Section: Why Assess Water Needs?mentioning
confidence: 99%
“…The physical effects of water fetching have traditionally focused on the musculoskeletal impacts of carrying containers on the head (Geere, Bartram, et al, 2018; Porter et al, 2013). But water fetching has been found to be associated with a wide range of physical injuries, such as neck and leg pain, and mental health effects (Geere, Cortobius, Geere, Hammer, & Hunter, 2018), as well as maternal and child health risks (Geere & Hunter, 2020).…”
Section: Resultsmentioning
confidence: 99%